Erastus Corning : Merchant and Financier, 1794-1872 - Neu, Irene D. (Cornell University Press, 2018)
Creator and first president of the New York Central Railroad, Erastus Corning was one of the outstanding American businessmen of the midnineteenth century. Merchant and manufacturer, railroad promoter, land speculator, financier, and politician, he built a fortune from nothing to eight million dollars. In her skillfully written biographical study, Professor Neu tells the story of this man's varied and highly successful career and, in the telling, traces the pattern of domestic mercantile activity in the early and middle years of the past century.Corning is best remembered as the "architect" of the New York Central Railroad, and the author has been particularly successful in explaining the process by which he lost control of it to Cornelius Vanderbilt. Here also is a unique account of the activities of a state bank in the 1830's, both interesting and important because it was one in "the wave of state bank incorporations" that attended Jackson's attack on the Bank of the United States. Professor Neu has done a thorough job of research in the sources and treated her material with historical detachment. Lucid in organization and style, her able work answers the need for a full-scale treatment of a man whose reputation was nationwide.